Immunological and classical subtypes of oral premalignant lesions. (2nd December 2018) - Foy, Jean-Philippe; Bertolus, Chloé; Ortiz-Cuaran, Sandra; Albaret, Marie-Alexandra; Williams, William N; Lang, Wenhua; Destandau, Solène; Souza, Geneviève De; Sohier, Emilie; Kielbassa, Janice; Thomas, Emilie; Deneuve, Sophie; et al.
ABSTRACT: Oral squamous cell carcinoma (OSCC) is a major cause of cancer-associated morbidity and mortality and may develop from oral premalignant lesions (OPL). An improved molecular classification of OPL may help refining prevention strategies. We identified two main OPL gene-expression subtypes, named immunological and classical, in 86 OPL (discovery dataset). A gene expression-based score was then developed to classify OPL samples from three independent datasets, including 17 (GSE30784), 13 (GSE10174) and 15 (GSE85195) OPLs, into either one of the two gene-expression subtypes. Using the single sample gene set enrichment analysis, enrichment scores for immune-related pathways were different between the two OPL subtypes. In OPL from the discovery set, loss of heterozygosities (LOH) at 3p14, 17p13, TP53, 9p21 and 8p22 and miRNA gene expression profiles were analyzed. Deconvolution of the immune infiltrate was performed using the Microenvironment Cell Populations-counter tool. A multivariate analysis revealed that decreased miRNA-142-5p expression ( P = 0.0484) and lower T-cell, monocytic and myeloid dendritic cells (MDC) immune infiltration (T-cells, P = 0.0196; CD8 T cells, P = 0.0129; MDC, P = 0.0481; and monocytes, P = 0.0212) were associated with oral cancer development in the immunological subtype only. In contrast, LOH at 3p14 ( P = 0.0241), 17p13 ( P = 0.0348) and TP53 ( P = 0.004) were associated with oral cancer development in the classical subtype only. In conclusion, we identified 2 subtypes of OPLs, namely immune and classical, which may benefit from different and specific personalized prevention interventions.